2016
DOI: 10.1016/j.jcrs.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Polychromasia capsulare: Determining the cause of multicolored iridescence of the anterior lens capsule

Abstract: None of the authors has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…These findings suggested the association between the nanoarchitecture of the anterior lens capsule Correspondence and the iridescence of polychromasia capsulare. 3 Moreover, Mir et al suggested that iridescence is possibly caused by light diffraction through a region of capsule composed of variant of fibrillin or of collagen giving this polychromatic pattern. Peripheral polychromatic region was corresponded to the area of the capsule that is rich in fibrillin, as opposed to the central part, which is predominantly composed of collagen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested the association between the nanoarchitecture of the anterior lens capsule Correspondence and the iridescence of polychromasia capsulare. 3 Moreover, Mir et al suggested that iridescence is possibly caused by light diffraction through a region of capsule composed of variant of fibrillin or of collagen giving this polychromatic pattern. Peripheral polychromatic region was corresponded to the area of the capsule that is rich in fibrillin, as opposed to the central part, which is predominantly composed of collagen.…”
mentioning
confidence: 99%
“…8 Interestingly, iridescence in our case manifested only after phacoemulsification cataract surgery but not before, and it was only unilateral. This could be explained by 1 of 2 mechanisms: First, residual lens epithelial cells of anterior capsule proliferation, migration on the posterior capsule, and normal and abnormal differentiation giving different light diffraction, but this residual lens epithelial cells theory was rejected by Osher et al 3 Second mechanism is that disruption of blood-aqueous barrier in patients with uveitis allows inflammatory cells, mediators, and proteins to enter the usually immune-privileged intraocular environment, resulting in deposition of exudative materials with a specific nanostructure behind IOL and forming diffraction grating and reflection of light through semitransparent multilayers.…”
mentioning
confidence: 99%